DEVELOPMENT OF THE PCR-BASED PROTOCOL FOR DIAGNOSIS OF BRUCELLOSIS WITH DETECTION ON AGAROSE GEL - Abisheva, G.D.; Kairzhanova, A.D.; Shevtsova, E.S.; Karibaev, T.B.; Dzhailbekova, A.S.; Sytnik, I.I.; Tjulegenov, S.B.; Shevtsov, A.B; Mukanov, K.K. (Eurasian Journal of Applied Biotechnology, 2014)
Despite significant progress in monitoring and control of infectious diseases, brucellosis remains one of the most important zoonotic infections with a vast distribution area. Efficiency of anti-brucellosis campaign depends on the effectiveness of diagnostic procedures that must be focused on early detection of infection. In Kazakhstan, serological methods are used for mass confirmatory analysis of brucellosis. These methods include complement fixation (CF) and enzyme-linked immunosorbent assay (ELISA). High infection rate among domestic animals gives rise to widespread distribution of the disease among people. The aim is to develop a PCR protocol for application in veterinary laboratories. As a result of this study, the new protocol for PCR detection of Brucella is presented in this article. Sensitivity of the PCR protocol in detection of Brucella DNA was 21 genome equivalents. Determination of the specificity of PCR by analyzing a DNA sample 78 showed its specificity level of about 100%.